The contribution of transposable elements to Bos taurus gene structure - Almeida, Luciane M.; Silva, Israel T.; Silva, Wilson A.; Castro, Juliana P.; Riggs, Penny K.; Carareto, Claudia M.; Amaral, M. Elisabete J. (Elsevier B.V., 2007)
In an effort to identify the contribution of TEs to bovine genome evolution, the abundance, distribution and insertional orientation of TEs were examined in all bovine nuclear genes identified in sequence build 2.1 (released October 11, 2005). Exons, introns and promoter segments (3 kb upstream the transcription initiation sites) were screened with the RepeatMasker program. Most of the genes analyzed contained TE insertions, with an average of 18 insertions/gene. The majority of TE insertions identified were classified as retrotransposons and the remainder classified as DNA transposons. TEs were inserted into exons and promoter segments infrequently, while insertion into intron sequences was strikingly more abundant. The contribution of TEs to exon sequence is of great interest because TE insertions can directly influence the phenotype by altering protein sequences. We report six cases where the entire exon sequences of bovine genes are apparently derived from TEs and one of them, the insertion of Charlie into a bovine transcript similar to the zinc finger 452 gene is analyzed in detail. The great similarity of the TE-cassette sequence to the ZNF452 protein and phylogenetic relationship strongly suggests the occurrence of Charlie 10 DNA exaptation in the mammalian zinc finger 452 gene. (c) 2006 Published by Elsevier B.V.
Keywords: bovine; exaptation; domestication; Charlie transposon